Above‐ground woody carbon sequestration measured from tree rings is coherent with net ecosystem productivity at five eddy‐covariance sites. Issue 4 (11th November 2013) - Babst, Flurin; Bouriaud, Olivier; Papale, Dario; Gielen, Bert; Janssens, Ivan A.; Nikinmaa, Eero; Ibrom, Andreas; Wu, Jian; Bernhofer, Christian; Köstner, Barbara; Grünwald, Thomas; Seufert, Günther; et al.
Summary Attempts to combine biometric and eddy‐covariance (EC) quantifications of carbon allocation to different storage pools in forests have been inconsistent and variably successful in the past. We assessed above‐ground biomass changes at five long‐term EC forest stations based on tree‐ring width and wood density measurements, together with multiple allometric models. Measurements were validated with site‐specific biomass estimates and compared with the sum of monthly CO2 fluxes between 1997 and 2009. Biometric measurements and seasonal net ecosystem productivity (NEP) proved largely compatible and suggested that carbon sequestered between January and July is mainly used for volume increase, whereas that taken up between August and September supports a combination of cell wall thickening and storage. The inter‐annual variability in above‐ground woody carbon uptake was significantly linked with wood production at the sites, ranging between 110 and 370 g C m−2 yr−1, thereby accounting for 10–25% of gross primary productivity (GPP), 15–32% of terrestrial ecosystem respiration (TER) and 25–80% of NEP. The observed seasonal partitioning of carbon used to support different wood formation processes refines our knowledge on the dynamics and magnitude of carbon allocation in forests across the major European climatic zones. It may thus contribute, for example, to improved vegetation model parameterization and provides an enhanced framework to link tree‐ring parameters with EC measurements.